2001
DOI: 10.1038/sj.leu.2402231
|View full text |Cite
|
Sign up to set email alerts
|

Early increase in DcR2 expression and late activation of caspases in the platelet storage lesion

Abstract: Platelet transfusion is widely used to prevent bleeding in patients with severe thrombocytopenia. The maximal storage duration of platelet concentrates is usually 5 days, due to the platelet storage lesion that impairs their functions when stored for longer times. Some of the morphological and biochemical changes that characterize this storage lesion are reminiscent of cell death by apoptosis. The present study analyzed whether proteins involved in nucleated cell apoptosis could play a role in the platelet sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 53 publications
5
36
1
Order By: Relevance
“…[42][43][44][45][46][47] The possibility of stored platelets undergoing secondary necrosis may partly explain the inability of apoptosis inhibitors to maintain the viability of stored platelet concentrates. 48,49 Would agents that preserve mitochondrial function improve the viability of stored platelets? Much of the current effort into improving the viability of stored platelet concentrates has focused on reducing platelet activation, maintaining pH, buffering lactate production and enhancing gas exchange.…”
Section: Apoptotic and Necrotic Death Pathways: Implications For The mentioning
confidence: 99%
“…[42][43][44][45][46][47] The possibility of stored platelets undergoing secondary necrosis may partly explain the inability of apoptosis inhibitors to maintain the viability of stored platelet concentrates. 48,49 Would agents that preserve mitochondrial function improve the viability of stored platelets? Much of the current effort into improving the viability of stored platelet concentrates has focused on reducing platelet activation, maintaining pH, buffering lactate production and enhancing gas exchange.…”
Section: Apoptotic and Necrotic Death Pathways: Implications For The mentioning
confidence: 99%
“…Also, it has been reported that melanoma cells are frequently resistant at the time of surgical excision, but regain sensitivity in cell culture (Nguyen et al, 2001). A similar effect has been demonstrated in platelets that have been stored for transfusion, where there is an early increase in the expression of DcR2, but this increase in expression is not enough to protect platelets from lesion, caused by apoptosis and caspase activation of these cells (Plenchette et al, 2001). It is therefore important to develop an understanding of the factors that lead to sensitivity or resistance of tumour cells to Apo2L/TRAIL.…”
Section: Discussionmentioning
confidence: 69%
“…Storage for longer periods of time leads to impaired platelet function, known as platelet storage lesion (PSL) [20]. Some of the morphological and biochemical aspects of the PSL have been compared to apoptotic events [21,22] and it is interesting to note that glucose deprivation is known to lead to apoptosis [23,24]. It has been shown that calpain is activated during platelet storage and that several signalling molecules translocate to the cytoskeleton after stress induced calpain activation indicating a critical role of the cytoskeleton in platelet ageing [14].…”
Section: Discussionmentioning
confidence: 99%